Development of a drug-eluting intraocular lens to deliver epidermal growth factor receptor inhibitor gefitinib for posterior capsule opacification prophylaxis. Issue 2 (March 2021) - Kassumeh, Stefan; Kueres, Alexander; Hillenmayer, Anna; von Studnitz, Annabel; Elhardt, Carolin; Ohlmann, Andreas; Priglinger, Siegfried G; Wertheimer, Christian M
Purpose: Different molecular targets, such as the epidermal growth factor receptor, have been identified for the prophylaxis of posterior capsule opacification. This led to the proposal of several drugs, yet drug delivery into the capsular bag remains challenging. The intraocular lens as a drug delivery device would provide a convenient method to allow drug release in the location needed. This is to evaluate the effect of a drug-eluting intraocular lens using an epidermal growth factor receptor inhibitor. Methods: Hydrophobic and hydrophilic intraocular lenses were coated with gefitinib using the dip coating technique. The cellular response on the modified intraocular lenses was tested in a human lens epithelial cell line (FHL-124) in an anterior segment model. Furthermore, modified intraocular lenses were implanted into human capsular bags ex vivo . Drug release was determined as well as the biocompatibility on human corneal endothelial cells. Unmodified intraocular lenses served as controls. In addition, immunofluorescence staining with fibronectin as a marker for fibrotic response was conducted. Results: Both coated hydrophilic and hydrophobic intraocular lenses could attenuate the cell growth of FHL-124 cells in the human capsular bag in comparison to the unmodified controls. Furthermore, gefitinib-soaked intraocular lenses showed a constant drug release over the first 10 days. No reduction in cell viability of corneal endothelial cells occurred. A decrease in fibronectin expression under gefitinib treatment could be observed. Conclusion: In vitro epidermal growth factor receptor seems to be a valuable target for the prevention of posterior capsule opacification. The gefitinib-eluting intraocular lens in this study could inhibit cell growth in non-toxic concentrations.